A case report: interstitial pneumonia following treatment of gastric cancer with sintilimab in combination with S-1 - Zhu, Pei; Sun, Qingming; Xu, Sheng; Dong, Wanhui (Frontiers in Pharmacology, 2025)
BackgroundInterstitial pneumonia is a group of pathologies affecting the pulmonary interstitium, characterized by interstitial fibrosis and extensive alveolar consolidation. This disease can extend to the surrounding blood vessels and pulmonary interstitium, sometimes affecting the entire lung, resulting in functional limitations, including restrictive ventilatory defect, impaired gas exchange, and hypoxemia. Severe interstitial pneumonia can lead to death. Antitumor drugs can induce interstitial pneumonia. Sintilimab is an immune checkpoint inhibitor, a recombinant fully human immunoglobulin G-type programmed death protein-1 monoclonal antibody inhibitor. S-1 is a compound preparation consisting of gimeracil, oteracil potassium, and ftorafur. There have been cases of interstitial pneumonia caused by treatment with sintilimab or S-1 in clinical settings, but no cases of interstitial pneumonia caused by treatment with a combination of sintilimab and S-1 have been reported.Case reportA patient diagnosed with gastric cancer underwent nine courses of treatment using a chemotherapy regimen of combined oxaliplatin S-1., Due to severe bone marrow suppression and gastrointestinal adverse reactions, the treatment was switched to sintilimab in combination with S-1therapy., This change resulted in the development of interstitial pneumonia, as revealed by non-contrast chest Computed Tomography scans. Following a review of blood test results and a multidisciplinary consultation, we suspect that the interstitial pneumonia may have been caused either by Sintilimab alone or by the combined effects of sintilimab and S-1. The treatment was discontinued, and after receiving adequate glucocorticoid therapy, the pulmonary lesions showed slight improvement.ConclusionThis case provides a clinical reference, indicating that prior touse of sintilimab in combination with S-1 antitumor regimen, a comprehensive baseline assessment should be conducted, including blood routine examination, enzyme tests, and pulmonary imaging examination, with close monitoring of the patient’s pulmonary condition. If drug-induced lung injury is suspected, the medication should be discontinued immediately, and appropriate treatment should be initiated promptly.